Human milk cortisol is inversely associated with infant BMI and mediates the association between maternal plasma and infant salivary cortisol concentrations - Kruger, Ana Luz (2025)
Purpose The pathways through which milk cortisol affects infant body weight and adiposity remain poorly understood. Aims To assess the influence of maternal weight status on maternal cortisol concentrations and infant outcomes; to evaluate the relationship between maternal plasma and milk cortisol concentrations and infant salivary cortisol, body weight and adiposity during the first 3 months of life in a cohort of exclusively breastfed infants; to determine whether milk cortisol mediates these effects; and to explore the association between infant salivary cortisol and measures of body weight and adiposity. Methods In this prospective observational study, we measured cortisol concentrations in plasma and milk samples from lactating women at 10 days (n = 68) and 3 months postpartum (n = 34), and in saliva samples from their 3-month-old infants (n = 34). Multiple linear regression and mediation analysis were conducted to determine the relationship between maternal characteristics and infant anthropometric measurements or salivary cortisol concentration and whether they were mediated by milk cortisol. Results Plasma and milk cortisol concentrations were inversely associated with gestational weight gain and postpartum weight retention at 10 days postpartum. Maternal plasma and milk cortisol concentrations were directly with infant salivary cortisol concentration [Beta (95% CI): 0.05 (0.00, 0.09), p = 0.038; 0.95 (0.51, 1.39), p < 0.001], and inversely associated with infant BMI z-score [Beta (95% CI): −0.11 (−0.17, −0.04), p = 0.004; −1.04 (−1.69, −0.39), p = 0.003] at 3 months of lactation, the former mediated by milk cortisol (p = 0.039). Infant salivary cortisol was not associated with body weight and adiposity at 3 months of lactation. Conclusion Our study shows that in exclusively breastfed infants, milk cortisol is inversely associated with BMI z-score and influences salivary cortisol at 3 months postpartum. Further research is warranted to explore the mechanisms involved and how these interactions evolve across different stages of lactation.